Pengaruh Harga Dan Persepsi Atribut Produk Terhadap Keputusan Pembelian Sepatu Converse (Studi Kasus Di Darmo Trade Center Surabaya) - Putu Herry Sunarya, ; Septa Dian Megasari, (Bisnis dan Manajemen, 2010)
Shoes are included to shopping goods as we know before consumers buy usually needs to consider according to price and attributes product congruency. Consumers tend to considers attributes product and price depend on information they got and finally can shape consumers perception to attributes product and price its self and finally it can shape buying decision. This research is purposed to analyze the influence of price and attributes product perception of converse shoes to buying decision not only stimulant but also partial. Hypothesis is used in this research is a) it is guessed price and attributes product perception is influenced stimulant to buying decisions and b) it is guessed price and attributes product perception is influenced partial to buying decisions. Sample is determined by non probability sampling method with accidental sampling technique from population consumers who ever bought converse shoes in Darmo Trade Center Surabaya. Data primer is collected by questioner through survey and interview. This Sample is consisted of 100 respondents who use and ever bought converse shoes in Darmo Trade Center. Data analyzed is done by Multiple Linear Regressions.